Pengaruh Reward dan Punishment Terhadap Kinerja Karyawan Muslim dalam Persepektif Bisnis Islam (Studi PT. Honda Bintang Motor Gading Cempaka Kota Bengkulu) - Aji Dwiansyah; Yosy Arisandi; Evan Stiawan (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This research aims to analyze the effect of providing rewards and punishment on the performance of Muslim employees from an Islamic business perspective at PT. Honda Bintang Motor Gading Cempaka Bengkulu City. Employee performance is an important factor in the company's success, so an effective human resource management strategy is needed, one of which is through implementing a reward and punishment system that is in accordance with the principles of justice and Islamic ethics. This research uses a quantitative approach with a quantitative descriptive research type. Data was obtained by distributing questionnaires to 30 employees as respondents using a purposive sampling technique. Data analysis was carried out using multiple linear regression with the help of the IBM SPSS version 25 program. The research results showed that partially rewards had a positive and significant effect on employee performance, as did punishment which also had a positive and significant effect on employee performance. Simultaneously, reward and punishment have a significant effect on the performance of Muslim employees. The coefficient of determination value shows that reward and punishment are able to explain 65% of the variation in employee performance, while the remainder is influenced by other factors outside the research model. These findings show that implementing rewards and punishment that are fair, proportional and in accordance with Islamic business values ​​can improve employee performance optimally.